Modelación de la emisión de compuestos orgánicos volátiles en sistemas de aereación mediante un modelo de dos zonas simplificado - Durán Herrera, Esteban (2009)
A new simplified mass-transfer model was developed to describe the volatile organic compounds (VOC) emission rates from diffused aeration systems. The model takes into consideration that the VOC mass transfer occurs in two separate mass-transfer zones instead of lumping the overall VOC transfer in the whole aeration tank as is done in the conventional ASCE-based model. A series of batch VOC emission tests were performed in a 1000 l tank equipped with a fine pore diffuser at 0,50 to 1,33 - 10-3 normal m3/s diffused air flow rate and a water temperature of 293 K. The unsteady-state dissolved concentrations of p-xylene, benzene, toluene, trichloroethylene and tetrachlorethylene were measured during the tests and these data were used to find the proportional coefficient Î¨ and with it, the volumetric mass-transfer coefficients of the VOCs. It was found that the Î¨ coefficients were not dependent upon the diffused air flow rate, but do depend on the nature of the volatile compound used. A semiempirical set of equations that predict successfully the Î¨ coefficients based on the critical volume and the normal boiling temperature of the compound was found. It was concluded that the new model provides better insight of the VOC mass transfer process and requires only oxygen aeration performance data, besides the critical volume and the normal boiling point of the compound, to predict accurately the VOC emission rates.